Different Histories of the Present. On the Spanish Reception of Michel Foucault's Surveiller et Punir and the Issue of Political Prisoners. Issue 1 (23rd January 2018) - Herrmann, Lucia
In the mid-1970s Foucault's work on the birth of the prison entered contemporary debates about the prison in Spain in various instances. Reading Foucault's writings and their Spanish reception next to each other, it becomes clear that one question central to the Spanish prison debates at the time was hardly mentioned in Surveiller et Punir : namely, the relationship between political and non-political prisoners. After a brief contextualization of Spanish prison debates in the 1970s and their reference to Foucault's work, this paper first outlines in what way the issue of political prisoners was (in the Spanish case) or was not (in Foucault's prison study) discussed and why. Based on this comparison the paper clarifies the link between past and present in Foucault's approach of a "history of the present." It then draws on an interview where Foucault did reflect on the issue of prisoner categories and concludes with a suggestion for productively using Foucault's methods as tools to analyze historically changing debates about the issue of political prisoners as a history of contingent problematizations.